Hubungan antara Pengasuhan Orang Tua dengan Kecerdasan Emosional Anak di PAUD Puti Bungsu SKB I Tanah Datar - Dwi Puja Andani; Setiawati Setiawati; Wisroni Wisroni (Universitas Negeri Padang, 2018)
This research is motivated by the low of early age children who have not been able to control their emotions in PAUD Puti Bungsu SKB 1 Tanah Datar. This is allegedly due to the lack of parenting provided by parents to their children. The purpose of this study are: (1) describes parenting by the parents to early childhood, (2) describes the emotional intelligence of early childhood, and (3) how the relationship between parenting by parents with early emotional intelligence in early childhood PAUD Puti Bungsu SKB I Tanah Datar. The type of this research is descriptive correlation, population in research amount to 30 people. Samples were taken as much as 80% with the number of samples is 24 people. The sampling technique using simple random sampling. Data collection techniques used are questionnaires, while data collection tools using questionnaires. Data analysis techniques using the formula percentage and Product Moment. The results of the study found that (1) the parenting of the children is still poor, (2) the early childhood emotional intelligence in early childhood PAUD Puti Bungsu SKB I Tanah Datar still looks very low, and (3) there is a significant relationship between parenting with the emotional intelligence of children in paud the youngest son of SKB I Tanah Datar.